Estudo hidrogeológico e geofísico do aquífero fissural no campus da UFMT - Cuiabá - MT - Hernández, Andrés Silva (2018)
The fissure aquifers represent one of the most difficult questions of Hydrogeology, because they are anisotropic and heterogeneous aquifers, in which the groundwater circulates by cracks in the rocks. Such fissures are mainly composed of ruptured structures generated by tectonic action, such as fractures and faults. The UFMT Campus, in Cuiabá, overlaps with a fissure aquifer installed in metasedimentary rocks of the Cuiabá Group. This aquifer is responsible for the water supply of the campus with a contribution of 77% and, to this day, has not been properly studied. This research is aimed to define the hydraulic and structural characteristics of the aquifer; determine the preferred directions of underground water flow; and define favorable points for future drilling, considering that the location of a well represents a very complex task due to the various factors that interfere in the water productivity of structures that cross fractured crystalline rocks. However, the application of geophysics to the groundwater study provides the data needed to prospect this important resource, resulting in optimum productivity in subsequent perforations, higher water availability and lower energy consumption in the pumping. The preferred directions of underground water flow in the study area were determined by geophysical tests using the method of Resistivity with Dipole-Dipole arrangement in conjunction with measurements of outcrops of the rocky structures, as well as photointerpretation of aerial photographs. The hydraulic characteristics of the wells installed on The UFMT Campus were defined through an analysis of pumping tests performed by available as files this university. These tests consisted in the pumping of the wells, with follow-up of the lowering of the level of water inside these same wells. The result of this study provides adequate position for future drillings and what can expected of the potentialities of the new wells.